Pediatrics Poliomyelitis - O.K. Koloskova; L.A. Ivanova; U.I. Marusyk (Aktualʹnaâ Infektologiâ, 2016)
The paper deals with the problems of diagnosis, differentiated diagnosis, dispensary for disease, prevention and treatment of poliomyelitis in children. There are presented the WHO guidelines on poliomyelitis for Ukraine.